The Differences Between Hormonal Pills and Injection Contraception Adverse Effect: Pekanbaru Puskesmas Case Study - Lasiah Susanti; Erick Caessarrani A (International Journal of Healthcare Research, 2018)
Background: In Indonesia majority contraception participant using hormonal methods, consist of pills and injection methods. Whereas, hormonal contraception methods causing various adverse effects. Menstrual cycle irregularity, metrorhagia, menorhagia, nausea, headache, breast tenderness, weight gain, negative mood changes, libido changes, acne, palpitation, hair loss Objectives: To acknowledge the adverse effect differences between pills and injections hormonal contraception Methodology: The design of this study is cross sectional, using sample from Puskesmas in Pekanbaru. Data was analyze with cross tabulation, and Independent T-test.  Results: Adverse effect that have been found according to its quantities: weight gain (74%), Menstrual cycle irregularity (53%) , mood changes (53%), libido changes (47%), hair loss (47%), headache (24%), nausea (21%), acne (21%), metrorhagia (21%), menorhagia (18%) palpitation (6%). Cross tabulation show that most adverse effect was found on injection hormonal contraception Discussions: Hormonal contraception adverse effect commonly explained by its effect on metabolic and cardiovascular system. Metabolically, hormonal contraception affecting many target organs with progestin as mostly substance in charge as cause for adverse effect Conclusions: There is significant differences adverse effect between hormonal injections progestin only contraception methods and hormonal pills estradiol levonorgestrel combination. All adverse effect occur more excessively (18%) on hormonal injection progestin only methods.